2015
DOI: 10.1371/journal.pntd.0003770
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and Benznidazole-Mediated Prevention of Trypanosoma cruzi-Induced Endothelial Activation: Role of 15-epi-lipoxin A4 in the Action of Simvastatin

Abstract: Trypanosoma cruzi is the causal agent of Chagas Disease that is endemic in Latin American, afflicting more than ten million people approximately. This disease has two phases, acute and chronic. The acute phase is often asymptomatic, but with time it progresses to the chronic phase, affecting the heart and gastrointestinal tract and can be lethal. Chronic Chagas cardiomyopathy involves an inflammatory vasculopathy. Endothelial activation during Chagas disease entails the expression of cell adhesion molecules su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…Recently, our group reported that aspirin decreases EC activation and myocardial inflammation in a T. cruzi-infected murine model via the production of 15-epi-LXA4 (16). In addition, simvastatin and benznidazole prevent EC activation in human umbilical vein endothelial cells (HUVECs), decreasing ECAM expression on the cell surface, an effect mediated by 15-epi-LXA4 (17). However, the role of simvastatin in endothelial activation and its link with 15-epi-LXA4 in vivo remain to be studied.…”
mentioning
confidence: 99%
“…Recently, our group reported that aspirin decreases EC activation and myocardial inflammation in a T. cruzi-infected murine model via the production of 15-epi-LXA4 (16). In addition, simvastatin and benznidazole prevent EC activation in human umbilical vein endothelial cells (HUVECs), decreasing ECAM expression on the cell surface, an effect mediated by 15-epi-LXA4 (17). However, the role of simvastatin in endothelial activation and its link with 15-epi-LXA4 in vivo remain to be studied.…”
mentioning
confidence: 99%
“…These manifestations are due to a chronic inflammatory process (Rassi et al, 2017). As part of these inflammatory processes, endothelial activation is observed, along with high expression of endothelial adhesion molecules that facilitate the recruitment of leukocytes that infiltrate the cardiac muscle (Campos‐Estrada et al, 2015). In addition, there is an increase in the production of thromboxane and platelet aggregation and the generation of local microthrombi and focal areas of ischemia, which may contribute to the appearance of fibrous tissue by myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group reported that acetylsalicylic acid (ASA) and simvastatin (Simv) modulate the expression of adhesion molecules in endothelial cells infected with T. cruzi (Molina‐Berrios et al, 2013a, b; Campos‐Estrada et al, 2015). Through this effect, the recruitment of inflammatory cells in infected tissues can be reduced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations